Protocol for the field experiment for variety calibration as an input in the yield estimation - Mathieu, Renaud; Quicho, Emma; Satapathy, Sushree (International Rice Research Institute, 2024)
Work package 4 maps rice areas using remote sensing, geographic information system (GIS), and crop modeling. This work builds on the Remote sensingbased Information and Insurance for Crops in Emerging economies (RIICE, http://www.riice.org/) co-developed by IRRI and implemented in South and Southeast Asian countries. RIICE technology is being introduced across Africa to enhance its rice monitoring system. A set of field protocols and forms was developed for seasonal field data collection. This protocol outlines the procedures for setting up a field experiment aimed at gathering phenological data for the calibration of rice varieties. The document provides a detailed, step-by-step guide to ensure the uniformity of the field experiment across all sites in Africa. In particular, the treatments/experimental design, the key dates and data to be collected and sampling procedure were thoroughly covered. The collected information is utilized to calibrate a specific rice variety, serving as a key input for the ORYZA model in a designated location.